Cucumis hystrix Chakrav. (Cucurbitaceae) - A new angiospermic record for Bangladesh - Uddin, Sarder Nasir; Khan, Bushra; Mirza, Momtaz Mohal (Bangladesh Journal of Plant Taxonomy, 2012)
DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13137 Bangladesh J. Plant Taxon. 19(2): 205-207, 2012 (December)